2007
DOI: 10.1007/s00362-006-0327-6
|View full text |Cite
|
Sign up to set email alerts
|

A stratified unrelated question randomized response model

Abstract: Randomized response, Stratified random sampling, Sensitive characteristics, Dichotomous population, Estimation of proportion,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…A stratified unrelated question RR model using Singh et al (1994) procedure, an improved unrelated question RR model for completely truthful reporting has been proposed. It has been shown that for the prior information given, the proposed stratified unrelated question RR model using Neyman allocation is more efficient in terms of variance than Kim and Elam (2007) unrelated question stratified RR model. A notable point in this study is that the proposed model is better than the one earlier considered by Kim and Elam (2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A stratified unrelated question RR model using Singh et al (1994) procedure, an improved unrelated question RR model for completely truthful reporting has been proposed. It has been shown that for the prior information given, the proposed stratified unrelated question RR model using Neyman allocation is more efficient in terms of variance than Kim and Elam (2007) unrelated question stratified RR model. A notable point in this study is that the proposed model is better than the one earlier considered by Kim and Elam (2007).…”
Section: Resultsmentioning
confidence: 99%
“…1. Since all the PRE values in Table 1 are greater than 100, our stratified unrelated question RR model using Neyman allocation is more efficient in terms of variance than Kim and Elam (2007) stratified RR model under the assumptions given and the prior information used. …”
Section: Theoremmentioning
confidence: 99%
See 2 more Smart Citations
“…Then randomized response (RR) technique is applied to each stratum. Many researchers have extended RR models to stratification such as [1,8,10,11,12,13,20,22]. In the following sub section we also extend proposed models to stratified sampling framework.…”
Section: Proposed Models Under Stratified Random Samplingmentioning
confidence: 99%